Maternal Mental Health in Late Pregnancy and Longitudinal Changes in Postpartum Serum Vitamin B-12, Homocysteine, and Milk B-12 Concentration Among Brazilian Women - Batalha, Mônica Araujo; dos Reis Costa, Paula Normando; Ferreira, Ana Lorena Lima; Freitas-Costa, Nathalia C.; Figueiredo, Amanda C. Cunha; Shahab-Ferdows, Setareh; Hampel, Daniela; Allen, Lindsay H.; Pérez-Escamilla, Rafael; Kac, Gilberto (Frontiers in Nutrition, 2022)
Background Little is known regarding the association between mental health distress during pregnancy and postpartum maternal serum biomarkers of vitamin B-12 status and milk B-12 concentration. Objective To evaluate the association between depressive and anxiety symptoms in the third trimester of pregnancy and changes in postpartum serum B-12, homocysteine, and B-12 milk concentration. Methods A total of 101 women (18–40 years) were studied in a prospective cohort with data at the third trimester of pregnancy (baseline) and three postpartum time-points (TPs): 2–8 days (TP1), 28–50 days (TP2), and 88-119 days (TP3) postpartum. B-12 concentrations in milk were measured by competitive chemiluminescent enzyme immunoassay at TP1, TP2, and TP3. Serum B-12 and homocysteine concentrations were evaluated at baseline, TP1, TP2, and TP3 by chemiluminescent immunoassays. Depressive and anxiety symptoms were measured with the Edinburgh Postnatal Depression Scale and the State-Trait Anxiety Inventory at baseline. Spearman's correlation test and multiple linear mixed-effect models were performed. Results The prevalence of depressive and anxiety state symptoms was 35.6 and 39.6% at baseline. High prevalence of low milk B-12 concentration (<310 pmol/L) were observed at TP1 (53.2%), TP2 (71.4%), and TP3 (71.1%). Women with anxiety symptoms at baseline presented higher median concentrations of serum homocysteine at TP1 and lower concentrations of serum and milk B-12 at TP2 compared with women without anxiety symptoms [8 (7; 9) vs. 6 (5; 8) and 266 (188; 369) vs. 332 (272; 413)]. Milk B-12 concentrations were positively and significantly correlated with maternal serum B-12 concentrations at different TP. Women with anxiety symptoms at baseline exhibited a decrease in daily postpartum homocysteine concentrations compared to women without anxiety symptoms (β = −0.002, SE = 0.001, p = 0.024). Conclusion Anxiety symptoms at the end of pregnancy were associated with longitudinal changes in maternal serum homocysteine concentrations during the first 3 months postpartum.